Mosaic variants in the LIM homeobox 1 (LHX1) gene contribute to Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome - Dina Kira; Soumia Brakta; Hyung Goo Kim; Jennifer Butler; Lynn P. Chorich; John A. Phillips; Lawrence C. Layman (Human Genetics, 2026)

In memoriam: Carl J. Carrano - Frithjof C. Küpper; Eleanor Carrano; Kenneth N. Raymond; Eric Miller; Ricardo Cruz-López; Ana Mijovilovich; Kyoko Yarimizu; Andrew Cooksy; Wes Harris; Shady A. Amin; Alison Butler; John C. Carrano (BioMetals, 2026)
This article is a celebration of the life and work of Carl J. Carrano who, from a childhood in Long Island, New York, built a career in bioinorganic chemistry, especially in the context of metal uptake and halogen metabolism in microbes and marine organisms.

Lace monitors scavenge the large carcass of an endangered eastern freshwater cod - Brendan C. Ebner; John St Vincent Welch; Leo M. Cameron; Jason Schaffer; Gavin L. Butler (Food Webs, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cyclones and skinny dolphins: adaptation pathways for Pacific communities under rapid global change - Matthew J. Colloff; James R.A. Butler; Nat Burke; John Morley; Lorrae van Kerkhoff; Zelda Hilly; Richard B. Makini-Purcell; Jamal Namo; Remy Barua; Kathryn Michie; Minnie Rafe; Slade Ririmae (Climate and Development, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Black Family Forest Owners in the Southeastern United States: A Case Study in Six Counties - Amanda Robillard; Cassandra Johnson Gaither; John Schelhas; Brett J Butler (Journal of Forestry, 2024)
The USDA Forest Service, National Woodland Owner Survey asks family forest owners (FFOs) about their attitudes and intentions regarding their forestland. Historically, the number of responses from Black or African American FFOs has been very low, but it is uncertain whether this is because of nonresponse bias or that there are relatively few Black FFOs. To get a better understanding of these FFOs and to test a method to increase response rates, an intensified survey effort was conducted in three southern states: Alabama, North Carolina, and South Carolina. Analyses indicate that Black FFOs have slightly different objectives, activities, and ownership structure for their forestland than their White counterparts, who have traditionally represented the majority of FFOs. Study Implications: By conducting an experiment to increase response rates from Black family forest owners to the National Woodland Owner Survey, we find traditional methodology is not effective. More importantly, we see this group has moderately different responses than their White counterparts. This has wide ranging implications for landowner assistance programs and other initiatives that have been designed on the premise that we are accurately capturing responses from all woodland owners.

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Biofilm-Mediated Fragmentation and Degradation of Microcrystalline Cellulose by Cellulomonas flavigena KU (ATCC 53703) - Emma S. Young; John D. Butler; Sara J. Molesworth-Kenyon; William J. Kenyon (Current Microbiology, 2023)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Correction to: Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)

Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)
Pumas ( Puma concolor ) were eliminated from most of the eastern USA a century ago. In the past couple of decades, their recovery in the West has increased puma dispersal into the Midwest, with some individuals even traveling to the East Coast. We combined published expert opinion data and a habitat suitability index in an analysis that identified 17 areas in the Upper Midwest, Ozarks, Appalachia, and New England that could potentially host puma populations in the future. Thirteen of these were larger than 10,000 km 2 and so likely to ensure a puma population’s long-term genetic health. Further, we quantified patch size, human density, livestock density, percent public land, and a sociocultural index reflecting wildlife values for comparing patches, as well as present a summary of current legislation relevant to puma management in the East. Our work may be useful in identifying suitable areas to restore pumas based not only on the quality of their biophysical habitat, but also on social values conducive to puma-human coexistence.

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Fractal domain refinement of models simulating hydrological time series - Abrar Habib; Adrian P. Butler; John P. Bloomfield; James P. R. Sorensen (Hydrological Sciences Journal, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Neurophysiological correlates of dual tasking in people with Parkinson’s disease and freezing of gait - Conor Fearon; John S. Butler; Saskia M. Waechter; Isabelle Killane; Simon P. Kelly; Richard B. Reilly; Timothy Lynch (Experimental Brain Research, 2021)

Stage‐dependent effects of river flow and temperature regimes on the growth dynamics of an apex predator - Rick J. Stoffels; Kyle E. Weatherman; Nick R. Bond; John R. Morrongiello; Jason D. Thiem; Gavin Butler; Wayne Koster; R. Keller Kopf; Nicole McCasker; Qifeng Ye; Brenton Zampatti; Ben Broadhurst (Global Change Biology, 2020)
In the world's rivers, alteration of flow is a major driver of biodiversity decline. Global warming is now affecting the thermal and hydrological regimes of rivers, compounding the threat and complicating conservation planning. To inform management under a non‐stationary climate, we must improve our understanding of how flow and thermal regimes interact to affect the population dynamics of riverine biota. We used long‐term growth biochronologies, spanning 34 years and 400,000 km 2 , to model the growth dynamics of a long‐lived, apex predator (Murray cod) as a function of factors extrinsic (river discharge; air temperature; sub‐catchment) and intrinsic (age; individual) to the population. Annual growth of Murray cod showed significant, curvilinear, life‐stage‐specific responses to an interaction between annual discharge and temperature. Growth of early juveniles (age 1+ and 2+ years) exhibited a unimodal relationship with annual discharge, peaking near median annual discharge. Growth of late juveniles (3+ to 5+) and adults (>5+) increased with annual discharge, with the rate of increase being particularly high in adults, whose growth peaked during years with flooding. Years with very low annual discharge, as experienced during drought and under high abstraction, suppress growth rates of all Murray cod life‐stages. Unimodal relationships between growth and annual temperature were evident across all life stages. Contrary to expectations of the Temperature Size Rule, the annual air temperature at which maximum growth occurred increased with age. The stage‐specific response of Murray cod to annual discharge indicates that no single magnitude of annual discharge is optimal for cod populations, adding further weight to the case for maintaining and/or restoring flow variability in riverine ecosystems. With respect to climate change impacts, on balance our results indicate that the primary mechanism by which climate change threatens Murray cod growth is through alteration of river flows, not through warming annual mean temperatures per se.

Minority Family Forest Owners in the United States - Sarah M Butler; John Schelhas; Brett J Butler (Journal of Forestry, 2020)
Family forest owners own more forestland in the United States than any other group. There have been no national studies of racial and ethnic minority family forest owners in the United States, in spite of increasing attention to diversity in forestry. Using the US Forest Service’s National Woodland Owner Survey data, we sought to better understand minority owners by looking at their characteristics, attitudes, and behaviors. Of the over 4 million family forest ownerships with 10+ ac in the United States, minorities comprise 6.6 percent of the ownerships and own 5.1 percent of the 265 million ac. Although many similarities exist between minority and nonminority owners, such as reasons for owning land and concerns, minority landowners tend to be more regionally located, have smaller forest holdings, are less likely to manage their forests, and are less likely to have participated in assistance programs. Broad insight into the attitudes and behaviors of minority family forest owners can help policymakers, program directors, and outreach coordinators begin to understand the needs of minority landowners, providing this historically underserved group with tools they need to attain their forest management and land-use goals. By increasing minority landowner engagement, we can hopefully slow the loss of land by minority landowners.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

A Three-Dimensional Mapping of the Ocean Based on Environmental Data - Roger Sayre; Dawn Wright; Sean Breyer; Kevin Butler; Keith Van Graafeiland; Mark Costello; Peter Harris; Kathleen Goodin; John Guinotte; Zeenatul Basher; Maria Kavanaugh; Patrick Halpin; et al. (Oceanography, 2017)

Development and testing of a micro wind tunnel for on-site wind erosion simulations - Craig L. Strong; John F. Leys; Mike R. Raupach; Joanna E. Bullard; Hélène A. Aubault; Harry J. Butler; Grant H. McTainsh (Environmental Fluid Mechanics, 2016)

The Application of Long-Lived Bivalve Sclerochronology in Environmental Baseline Monitoring - Juliane Steinhardt; Paul G. Butler; Michael L. Carroll; John Hartley (Frontiers in Marine Science, 2016)

Erratum to: Environmental Enrichment Mitigates Detrimental Cognitive Effects of Ketogenic Diet in Weanling Rats - John M. Scichilone; Kalyan Yarraguntla; Ana Charalambides; Jacob P. Harney; David Butler (Journal of Molecular Neuroscience, 2016)

Environmental Enrichment Mitigates Detrimental Cognitive Effects of Ketogenic Diet in Weanling Rats - John M. Scichilone; Kalyan Yarraguntla; Ana Charalambides; Jacob P. Harney; David Butler (Journal of Molecular Neuroscience, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

Isolation and characterization of an interactive culture of two Paenibacillus species with moderately thermophilic desulfurization ability - Jia Wang; Batzaya Davaadelger; Joelle K. Salazar; Robert R. Butler; Jean-François Pombert; John J. Kilbane; Benjamin C. Stark (Biotechnology Letters, 2015)

A simple and inexpensive enteric-coated capsule for delivery of acid-labile macromolecules to the small intestine - Darren S. Miller; Anne Michelle Parsons; John Bresland; Paul Herde; Duc Minh Pham; Angel Tan; Hung-yao Hsu; Clive A. Prestidge; Tim Kuchel; Rezaul Begg; Syed Mahfuzul Aziz; Ross N. Butler (Journal of Zhejiang University-SCIENCE B, 2015)

Optimal visual–vestibular integration under conditions of conflicting intersensory motion profiles - John S. Butler; Jennifer L. Campos; Heinrich H. Bülthoff (Experimental Brain Research, 2015)

Contributions of visual and proprioceptive information to travelled distance estimation during changing sensory congruencies - Jennifer L. Campos; John S. Butler; Heinrich H. Bülthoff (Experimental Brain Research, 2014)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

Effect of Potassium and Nitrogen Fertilizer on Switchgrass Productivity and Nutrient Removal Rates under Two Harvest Systems on a Low Potassium Soil - Maru K. Kering; Twain J. Butler; Jon T. Biermacher; Jagadeesh Mosali; John A. Guretzky (BioEnergy Research, 2013)

Switchgrass Biomass and Nitrogen Yield with Over-Seeded Cool-season Forages in the Southern Great Plains - Twain J. Butler; James P. Muir; Chengjun Huo; John A. Guretzky (BioEnergy Research, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Inheritance of resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) in five doubled-haploid populations of wheat - John P. Thompson; Rebecca S. Zwart; David Butler (Euphytica, 2012)

Estimation of spawning habitats of market squid ( Doryteuthis opalescens ) from field surveys of eggs off Central and Southern California - Louis D. Zeidberg; John L. Butler; Darlene Ramon; Anthony Cossio; Kevin L. Stierhoff; Annette Henry (Marine Ecology, 2012)
Like many other loliginid squid, Doryteuthis (Loligo) opalescens deposits egg cases on the ocean floor. Depending upon temperature, egg cases may persist for 5–12 weeks before the paralarvae hatch. Because of this relatively long duration and squid’s pelagic life history, egg cases provide a practical life stage to survey. During 2001–2002, squid egg beds in Monterey Bay, Carmel Bay, and around the California Channel Islands were surveyed using a remotely operated vehicle with the goal of delineating the habitat of egg beds that are spawned during active commercial fishing. Egg cases were highly aggregated and densities reached 1338 capsules m −2 . Squid eggs were significantly shallower in Central California. Egg cases occurred between 20 and 93 m around the Channel Islands, and in Central California they were between 13 and 61 m. The temperatures in both regions were similar (10–12 °C), with some eggs in Southern California found up to 14.4 °C. Ninety‐five percent of eggs were found on sand, suggesting that temperature and substrate are stronger behavioral cues than depth to stimulate spawning. Suitable spawning habitat was defined by three criteria: sandy benthic substrate, temperatures between 10 and 14.4 °C, and depths between 20 and 70 m when the first two criteria hold. Additionally, within this defined area, oxygen concentration is quantified. The greatest commercial landings of market squid occur in both Central and Southern California during a time of year when water temperatures of 10–12 °C are prevalent in the 20–70 m depth range.

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Multisensory integration in the estimation of walked distances - Jennifer L. Campos; John S. Butler; Heinrich H. Bülthoff (Experimental Brain Research, 2012)

Annual variation in soil respiration and its component parts in two structurally contrasting woody savannas in Central Brazil - Andre Butler; Patrick Meir; Gustavo Saiz; Leandro Maracahipes; Beatriz Schwantes Marimon; John Grace (Plant and Soil, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Auditory facilitation of visual-target detection persists regardless of retinal eccentricity and despite wide audiovisual misalignments - Ian C. Fiebelkorn; John J. Foxe; John S. Butler; Sophie Molholm (Experimental Brain Research, 2011)

Changes in Tundra Pond Limnology: Re-sampling Alaskan Ponds After 40 Years - Vanessa L. Lougheed; Malcolm G. Butler; Daniel C. McEwen; John E. Hobbie (Ambio, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Influences of forest harvest and environmental gradients on aquatic invertebrate communities of seasonal ponds - Mark A. Hanson; Shane E. Bowe; Fred G. Ossman; John Fieberg; Malcolm G. Butler; Richard Koch (Wetlands, 2009)

How the Conflict between American Psychiatry and Neurology Delayed the Appreciation of Cognitive Dysfunction in Multiple Sclerosis - Michelle A. Butler; John R. Corboy; Christopher M. Filley (Neuropsychology Review, 2009)

Activation amplitude patterns do not change for back muscles but are altered for abdominal muscles between dominant and non-dominant hands during one-handed lifts - Heather L. Butler; Cheryl L. Hubley-Kozey; John W. Kozey (European Journal of Applied Physiology, 2009)

Regional characterisation of hard‐bottom nursery habitat for juvenile Caribbean spiny lobster (Panulirus argus) using rapid assessment techniques - Rodney D. Bertelsen; Mark J. Butler; William F. Herrnkind; John H. Hunt (New Zealand Journal of Marine and Freshwater Research, 2009)
Shallow, hard‐bottom habitat constitutes approximately 30% of the coastal waters of south Florida, United States, yet it is a chronically understudied feature of the marine seascape in this region. In this study, we characterised the general biogeographic and structural features of shallow benthic hard‐bottom communities in the Florida Keys, and related those to the abundance of juvenile Caribbean spiny lobster (Panulirus argus) , the target of one of Florida's most economically valuable fisheries. We used rapid assessment techniques to survey more than 100 hard‐bottom sites in the Florida Keys to estimate the percentage bottom coverage of vegetation (seagrass and macroalgae) and the abundance of sponges, octocorals, hard corals, and other crevice‐bearing structures, as well as the abundance of juvenile lobsters. Using a multivariate statistical approach, we evaluated the relationship between habitat and size‐specific juvenile lobster abundance and quantitatively verified the existence of six generally accepted biogeographic subregions. Although the types of hard‐bottom shelters used by juvenile lobsters varied somewhat among these subregions, in all regions, branching‐candle sponges and octocorals were under‐used by lobsters, whereas loggerhead sponges, coral heads, and solution holes were over‐used (i.e., used more frequently than expected based on their availability). There was also an ontogenetic transition in the shelter preference of juvenile lobsters; small juveniles tended to occupy a variety of sponges, whereas large juveniles preferred hard structures such as coral heads and solution holes. This study yields the first quantitative biogeographic description of hard‐bottom communities of the Florida Keys, and confirms the suspected relationship between the structural features of hard‐bottom habitat and the value of these communities as nurseries for juvenile spiny lobster.

Is seagrass an important nursery habitat for the Caribbean spiny lobster, panulirus argus , in Florida? - Donald C. Behringer; Mark J. Butler; William F. Herrnkind; John H. Hunt; Charles A. Acosta; William C. Sharp (New Zealand Journal of Marine and Freshwater Research, 2009)
Caribbean spiny lobster (Panulirus argus) settle preferentially in macroalgal‐covered hard‐bottom habitat, but seagrass is more prevalent in Florida (United States) and the Caribbean, so even low settlement of lobsters within seagrass could contribute substantially to recruitment if post‐settlement survival and growth were high. We tested the role of seagrass and hard‐bottom habitats for P. argus recruitment in three ways. We first explored possible density‐dependent regulation of early benthic juvenile lobster survival within cages deployed in seagrass and hard‐bottom habitats. Second, we compared settlement and survival of P. argus in both habitats, by comparing the recovery of microwire‐tagged early benthic juveniles from patches of seagrass and hard‐bottom. Finally, we assessed the relative abundance of juvenile lobsters in each habitat by deploying artificial structures in seagrass sites and compared these data with data from similar deployments of artificial structures in hard‐bottom habitat in other years. More early benthic juvenile lobsters were recovered from cages placed in hard‐bottom than in seagrass, but mortality of the early benthic life stage was high in both habitats. In regional surveys, the mean number of lobsters recovered from artificial shelters deployed within seagrass was lower than in any year that we sampled hard‐bottom, indicating that fewer lobsters reside naturally in seagrass, particularly large juveniles >40 mm carapace length. The greater abundance (and likely survival) of juvenile P. argus that we observed in hard‐bottom habitat as opposed to seagrass, combined with previous studies demonstrating that postlarval P. argus are attracted to, settle in, and metamorphose more quickly in red macroalgae, confirm that macroalgae‐dominated hard‐bottom habitat appears to be the preferred and more optimal nursery for Caribbean spiny lobster.

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Applications of pedigree-based genome mapping in wheat and barley breeding programs - Mandy Christopher; Emma Mace; David Jordan; David Rodgers; Paul McGowan; Ian Delacy; Phillip Banks; John Sheppard; David Butler; David Poulsen (Euphytica, 2007)

Genetic mapping of sulfur assimilation genes reveals a QTL for onion bulb pungency - John McCallum; Meeghan Pither-Joyce; Martin Shaw; Fernand Kenel; Sheree Davis; Ruth Butler; John Scheffer; Jernej Jakse; Michael J. Havey (Theoretical and Applied Genetics, 2007)

Population dynamics, distribution, and growth rate of tilapia (Oreochromis mossambicus) in the Salton Sea, California, with notes on bairdiella (Bairdiella icistia) and orangemouth corvina (Cynoscion xanthulus) - Lucille L. Caskey; Ralf R. Riedel; Barry Costa-Pierce; John Butler; Stuart H. Hurlbert (Hydrobiologia, 2007)

Genetic mapping of a major gene affecting onion bulb fructan content - John McCallum; Andrew Clarke; Meeghan Pither-Joyce; Martin Shaw; Ruth Butler; Don Brash; John Scheffer; Ian Sims; Sjaak van Heusden; Masayoshi Shigyo; Michael J. Havey (Theoretical and Applied Genetics, 2006)

Shear stress and sediment resuspension in relation to submersed macrophyte biomass - William F. James; John W. Barko; Malcolm G. Butler (Hydrobiologia, 2004)

Assessment of DNA damage in C6 glioma cells after antidepressant treatment using an alkaline comet assay - Debbie Slamon; Tim Ward; John Butler; Vic Pentreath (Archives of Toxicology, 2001)

Cell compartmentalisation in planctomycetes: novel types of structural organisation for the bacterial cell - Margaret Lindsay; Richard Webb; Marc Strous; Mike Jetten; Margaret Butler; Rebecca Forde; John Fuerst (Archives of Microbiology, 2001)

Assessment of Regional Differences in Intestinal Fluid Movement in the Rat Using a Modified In Situ Single Pass Perfusion Model - Araz A. Raoof; Jackie Butler; John G. Devane (Pharmaceutical Research, 1998)

Genetic polymorphism of the IGHG3 gene in cattle - H. Rabbani; William R. Brown; John E. Butler; Lennart Hammarström (Immunogenetics, 1997)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)